PENGARUH EFIKASI DIRI TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PDAM SURYA SEMBADA KOTA SURABAYA - NARENDRA, GILANG (Jurnal Ilmu Manajemen (JIM), 2017)
Economic development in the era of globalization is much influenced by the increasingly strict business competition. Many of the challenges to be faced by the company. Companies need to keep the quality of the human resources (HR). PDAM Surya Sembada Kota Surabaya is the monopoly company engaged in the distribution of the water provider since 1976. This research aims to know and explain the influence of self efficacy against job satisfaction with motivation as intervening variables on PDAM Surya Sembada Kota Surabaya This research is a type of causal research that uses a quantitative approach with a population of as many as 71 people and sampling techniques using simple random sampling with the samples as many as 60 staff on PDAM Surya Sembada Kota Surabaya. Research results show that the efficacy of Self provide a positive influence and significantly to job satisfaction. Self efficacy influence positively and significantly to motivation. A positive and significant effect of motivation towards job satisfaction. s. Keywords: Self efficacy, motivation, job satisfaction